Digital Images Enhancement using Tiny Character Adjustment and Referenced Image Approach - Sajid Ullah, Khan; Najeeb Ullah, Khan; Chai, Soo See; Wang, Yin Chai (dline.info, 2016)
Digital image enhancement has been a hot topic during the past decades. In this paper, we have established a new approach for local gray contrast adjustment of tiny characters and global referenced base contrast enhancement approach to improve the contrast of degraded images. The proposed approach initially adjusts the contrast of tiny characters and then enhances the contrast of whole image by finding out some vital information from the histogram of the referenced image. The experimental results show that the proposed algorithm can adjust the tiny characters and increase the image contrast efficiently.